HAT2CH2 Score Predicts Systemic Thromboembolic Events in Elderly After Cardiac Electronic Device Implantation - Chen, Ju-Yi; Chen, Tse-Wei; Lu, Wei-Da (Frontiers in Medicine, 2021)
Background: The HAT2CH2 score has been evaluated for predicting new onset atrial fibrillation, but never for adverse systemic thromboembolic events (STE) in elderly. We aimed to evaluate the HAT2CH2 score and comparing to atrial high rate episodes (AHRE) ≥ 24 hours for predicting STE in older patients with cardiac implantable electronic devices (CIED) implantation. Methods: We retrospective enrolled 219 consecutive patients ≥ 65 years of age undergoing CIED implantation. The primary endpoint was subsequent STE. For all patients in the cohort, the CHA2DS2-VASc, C2HEST, mC2HEST, HAVOC, HAT2CH2 scores and AHRE ≥ 24 hours were determined. AHRE was defined as > 175 bpm lasting ≥ 30 seconds. Multivariate Cox regression analysis with time-dependent covariates was used to determine variables associated with independent risk of STE. Results: The median patient age was 77 years, and 61.2% of the cohort was male. During follow-up (median, 35 months), 16 STE occurred (incidence rate, 2.51/100 patient-years; 95% CI, 1.65–5.48). Multiple Cox regression analysis showed that the HAT2CH2 score (HR, 3.405; 95% CI, 2.272–5.104; p < 0.001) was an independent predictor for STE. The optimal HAT2CH2 score cutoff value was 3, with the highest Youden index (AUC, 0.907; 95% CI, 0.853–0.962; p < 0.001). The STE rate increased with increasing HAT2CH2 score (p < 0.001). Conclusions: This study is the first to show the prognostic value of the HAT2CH2 score for STE occurrence in older patients with CIEDs.